Islamic Law Understanding and Female Breadwinners: Gender Equity or Economic Demand? - Abdul Basith Junaidy; Rusli Rusli; Ahwan Fanani (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2025)
The female breadwinners among Muslim families nowadays is growing significantly, while male is obligated to provide for family needs in Islam. The number of female breadwinners in Kropak village, Probolinggo, for instance, has grown despite of its devout Muslims’ society. The article aims to reveal the reasons driving the rise of female breadwinners in Kropak Probolinggo and to analyze the phenomenon through the lens of Islamic law. The article employs a qualitative method, using case study approaches and uṣūl al-fiqh theory. Data are collected from in-depth interviews and documentation. The research shows that there are two reasons driving the phenomenon of female breadwinners in Kropak, Probolinggo, namely economic needs and lifestyle. The motives of women playing the role comprise the intention of supporting household expenses, caring for family members, or fulfilling the need for lifestyle. Some wives consider their breadwinner’s role as a necessary obligation, while others reluctantly accept it. In the lens of Islamic law, women are allowed to work, but Islamic scholars have different opinions on whether financial support by a wife is considered as a husband’s debt or as a condition allowing husbands to get rid of their responsibility. The article provides brief explanatios of the motives and Islamic law lens on female breadwinners’ phenomenon in Kropak Probolinggo.